How Learning a Musical Instrument Affects the Development of Skills - Adrian Hille; Jürgen Schupp (Institute for the Study of Labor (IZA), 2013)
Despite numerous studies on skill development, we know little about the causal effects of music training on cognitive and non-cognitive skills. This study examines how long-term music training during childhood and youth affects the development of cognitive skills, school grades, personality, time use and ambition using representative data from the German Socio-Economic Panel (SOEP). Our findings suggest that adolescents with music training have better cognitive skills and school grades and are more conscientious, open and ambitious. These effects do not differ by socio-economic status. Music improves cognitive and non-cognitive skills more than twice as much as sports, theater or dance. In order to address the non-random selection into music training, we take into account detailed information on parents, which may determine both the decision to pursue music lessons and educational outcomes: socio-economic background, personality, involvement with the child's school, and taste for the arts. In addition, we control for the predicted probability to give up music before age 17 as well as the adolescent's secondary school type. We provide evidence that our results are robust to both reverse causality and the existence of partly treated individuals in the control group.
Keywords: I21; J24; Z11; 330; music; cognitive and non-cognitive skills; educational achievement; SOEP